Modern Tendencies Indevelopment of Pedagogical Staff’s Professional Development System - Mirsolieva, Mukhabbat; Giyasova, Umida; Sultanov, Anvar (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article considers the essence of the training as the basis for teachers’ professional competence development. The comparative analysis of organization of teachers’ professional developmentin foreign countries.The efficient ways, methods and main types of organizing higher educational institution teachers’ professional developmentin different countries of the worldare described there.